MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP PECAHAN SEDERHANA MELALUI MEDIA KEPINGAN CD (COMPACT DISK) BAGI ANAK KESULITAN BELAJAR - Silviyah Yolanda Febrianti; Aulia Putri Marlani (P-2623-0291)
This Study begius with an assessment of research carried out inm man 2 mataram, there is a 9 year old boy with the initials X who can not recognize the conceptof fractional an optimal, where child have disability in naming fractions, indicatingfractions, and fractions matching numbers with symbols. This research alms toimprove understanding of the concept of simple fractions in the teartcing ofmathemations through the medium of CD (Compact Disk). Date analysis results in acondition and results of date between the condition seen that before treatment is givenusin the medium CD (Compact Disk) on baseline conditions, children’s ability to sayfractions. Children’s ability to demonstrate fractions. children ability to match thefraction with the symbol number. This proves medium CD (Compact Disk) can improvethe ability of understanding the concept of fraction for the child’s learning disability.For medium teachers should use there CD (Compact Disk) in the process of teachingand learning (PBM) for child learning disability at MAN 2 Mataram